Islamic finance: a growing industry the proliferation of interest-free finance - Kassim, Salina; Abd Majid, M. Shabri (Alfalah Consulting, 2009)
The recent financial crisis which originated from the 2007 US sub-prime crisis has been labelled as the worst financial crisis since the Great Depression by George Soros, Joseph Stiglitz, and the International Monetary Fund (IMF) (Jaffee, 2008; Tong and Wei, 2008). It has now become a full-blown global economic crisis.